Letter - Fawcett, Luke
001-0151-001 AMALGAMATED UNION of BUILDING TRADE WORKERS OF GREAT BRITAIN & IRELAND APPROVED SOCIETY N° 237 Luke Fawcett, General Secretary General Office "The Builders" Crescent Lane, South Side Clapham Common, London S.W.4 JC/WMc. Sir Walter Citrine,K.B.E., General Secretary, Trades Union Congress, Transport House, Smith Square, S.W. 1. 7th August, 1942. Dear Sir Walter, I attach a letter I have received from the Delegation in Great Britain of the General Workers' Union of Spain, and shall be glad if you will kindly inform me if this particular Organisation has received official recognition by the British Trade Union Congress. Yours sincerely, Luke Fawcett GENERAL SECRETARY 292/946/1/151